Confessions of a counterfeit farm girl - McCorkindale, Susan (New York : New American Library, 2008)
A laugh-out-loud memoir about a city slicker who discovers that Manolos and manure just don't mix.
Part 4. Farming, counterfeit farm girl style
Keywords: McCorkindale, Susan; Marketing executives -- New York (State) -- Biography